2022
DOI: 10.1007/s10643-022-01419-x
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Play Through Virtual Teaching: Challenges, Barriers, and Strategies

Abstract: Early childhood teachers routinely facilitate play-based learning experiences in their physical classrooms; however, the pivot to virtual teaching platforms created a barrier for providing age appropriate, play-based learning opportunities during the COVID-19 pandemic. There are few studies exploring how to promote play in the virtual classroom or what types of activities and learning experiences promote play in synchronous and asynchronous settings. Therefore, this study explored the barriers and challenges t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This rapid and abrupt change did not allow teachers to learn and prepare for the new mode of teaching and intensified job demands on teachers and families (Collie and Martin, 2016;Kwon et al, 2019Kwon et al, , 2022Allen et al, 2020). Research indicated that the vast majority of teachers did not have any experience teaching virtually, with limited training in this area before the pandemic (Ethridge et al, 2022). It is evident that many ECE teachers were committed to pivoting their teaching and used a variety of play-based strategies to facilitate children's learning through the virtual modality (Ethridge et al, 2022).…”
Section: Importance Of Teaching Adaptability For Ece Teachers During ...mentioning
confidence: 99%
See 4 more Smart Citations
“…This rapid and abrupt change did not allow teachers to learn and prepare for the new mode of teaching and intensified job demands on teachers and families (Collie and Martin, 2016;Kwon et al, 2019Kwon et al, , 2022Allen et al, 2020). Research indicated that the vast majority of teachers did not have any experience teaching virtually, with limited training in this area before the pandemic (Ethridge et al, 2022). It is evident that many ECE teachers were committed to pivoting their teaching and used a variety of play-based strategies to facilitate children's learning through the virtual modality (Ethridge et al, 2022).…”
Section: Importance Of Teaching Adaptability For Ece Teachers During ...mentioning
confidence: 99%
“…Research indicated that the vast majority of teachers did not have any experience teaching virtually, with limited training in this area before the pandemic (Ethridge et al, 2022). It is evident that many ECE teachers were committed to pivoting their teaching and used a variety of play-based strategies to facilitate children's learning through the virtual modality (Ethridge et al, 2022). They actively looked for resources and training and adopted various new strategies for teaching online effectively, such as modifying their traditional in-person classes via video conferencing platforms and creating new strategies to better engage children in developmentally appropriate ways (Allen et al, 2020;Ethridge et al, 2022;Kwon et al, 2022).…”
Section: Importance Of Teaching Adaptability For Ece Teachers During ...mentioning
confidence: 99%
See 3 more Smart Citations